Functions and Objectives of Hadiths on Education - Haidar Rifqi Ghassany; Ahmad Muhammad Tidjani (Penerbit Hellow Pustaka, 2024)
Hadith is the second foundation of Islamic law after the Koran. This hadith as a second source is shown by three things, namely; the Qur'an itself, the agreement (ijma`) of scholars, and the logic of common sense (ma`qul). The Koran emphasizes that the Prophet functioned to explain the meaning of Allah's words. Therefore, what the Prophet said must be followed, even the Prophet's behavior as an apostle must be imitated by the Muslims. This article finds that the function of hadith in the Qur'an is as bayan and muhaqiq (explanatory and strengthening) for the Qur'an. Both as bayan taqrir, bayan tafsir, takhshish al-’am, bayan tabdila. Not only that, this article also found that the hadith of the Prophet had established new laws that were not established by the Qur'an. Because in the Qur'an there are verses that command believers to obey absolutely what the Messenger of Allah commanded and prohibited, and threaten those who disagree with them.